An Evidence summary of postoperative pain management in spinal surgery (脊柱外科术后患者疼痛管理的证据总结) - XIANG Tingting (向婷婷); ZHENG Su (郑苏); XIE Xiaomin (谢晓敏) (中西医结合护理)
Objective To search and evaluate the evidence of postoperative pain management in spinal surgery so as to promote the standardized management of postoperative pain in patients with spinal surgery. Methods According to the "6S" evidence model, evidence of management of postoperative pain in spinal surgery were systematically searched from BMJ Best Practice, UpToDate, Cochrane library, Joanna Briggs Institute (JBI), National Guideline Clearinghouse(NGC), National Institute for Health and Clinical Excellence(NICE), Scottish Intercollegiate Guidelines Network(SIGN), Guidelines International Network(GIN), Registered Nurses’ Association of Ontario(RNAO), China Medical Network, PubMed, Web of science, Embase, EBSCO, Chinese Biomedical Medicine(CBM), China National Knowledge Infrastructure(CNKI), WanFang Data. Results A total of 10 articles were selected, including 1 clinical decisions, 2 evidence summary, 5 guidelines, 1expert opinion, 1 expert consensus, best evidences were summarized from the 5 aspects of pain evaluation, intervention, monitoring, education and organization. Conclusion This study summarized the best evidence of postoperative pain management in spinal surgery, which provided evidence for clinical application. In the process of evidence transformation, standards should be formulated to regulate the pain management behavior of medical staff in combination with clinical practice, so as to reduce postoperative pain in patients with spinal surgery and improve the quality of nursing (目的 检索并评价脊柱外科术后疼痛管理的相关证据, 以促进脊柱外科术后患者疼痛的规范化管理。方法 按照“6S”证据模型, 系统检索BMJ Best Practice、UpToDate、Cochrane library、Joanna Briggs Institute(JBI)、美国指南网、英国国家临床医学研究所指南网、苏格兰院际间指南网、国际网络指南网、加拿大安大略省注册护士协会网站、中国医脉通指南网、PubMed、Web of science、Embase、Ebsco、中国生物医学文献数据库、中国知网、万方数据库中关于脊柱外科术后疼痛评估管理的相关证据。结果 共纳入文献10篇, 包括临床决策1篇, 证据总结2篇, 指南5篇, 专家意见1篇, 专家共识1篇, 从疼痛评估、干预、监测、教育以及组织5个方面汇总最佳证据。结论 脊柱外科术后疼痛管理的证据总结可为临床应用提供循证依据, 在证据转化过程中应结合临床实际制定标准规范医护人员的疼痛管理行为, 降低脊柱外科术后患者疼痛, 提高护理质量。)